Burning characteristics and combustion wave model of AP/AN-based laser-controlled solid propellant. (15th August 2022) - Duan, Buren; Zhang, Haonan; Hua, Zuohao; Wu, Lizhi; Bao, Zijing; Guo, Ning; Ye, Yinghua; Shen, Ruiqi
Abstract: Laser-controlled solid propellant (LCSP) is a novel composite propellant that can achieve non-self-sustaining combustion under laser irradiation. Accordingly, a laser-controlled solid propellant based on AP/AN was designed. The thermal decomposition of LCSP was identified by TG/DSC coupled with MS/FTIR. It was found that the pyrolyzed gas products of LCSP were mainly composed of N2, N2 O, NH3, CO2, H2 O and HCl, etc. Furthermore, the combustion performance parameters including burning rate, ignition delay time, chamber pressure and conducting current of combustion products were tested. As the laser power density increased from 0.42 W/mm 2 to 1.06 W/mm 2, the burning rate increased from 0.51 mm/s to 0.88 mm/s and the platform pressure increased from 0.47 KPa to 0.78 KPa, while the ignition delay time decreased from 0.76 s to 0.23 s. Combining with the thermocouple, the combustion wave structure of LCSP can be divided into: pre-heating zone, condensed phase, optical-thermal reaction zone, dark zone and flame zone. Meanwhile, the high laser power density reduced the thickness of condensed phase and increased the thickness of dark zone. Finally, we inferred the combustion model of LCSP and proposed the hypothesis of critical combustion energy to explain the mechanism of non-self-sustaining combustion. Highlights: A non-self-sustaining combustion propellant (LCSP) is designed. The ignition process is controlled by active preignition reaction region. The combustion wave structure of LSCP can be divided into five zones. The combustion model is established based on the combustion wave structure. The hypothesis of critical combustion energy is proposed.